Ontological approach in the practice of the educational activity: paths’ formation of individual professional development of students - E. Y. Blago; I. A. Leshcheva; S. A. Scherban (Открытое образование (Москва))
Goal. The goal of the work is to develop the improved ontological model of the competency-oriented curricula, allowing constructing individual professional development paths of the students of particular educational profiles. Actuality of the developed model lies in the fact that the competence structure, existing in the framework of competency-oriented curricula, provided by the current Federal state educational standards does not allow differentiating within the same profile of learning the paths of individual professional development of the student, oriented to various career development directions within the general vocational orientation profile.Materials and methods. Individual educational paths can be differentiated according to the choice of the elective disciplines (as common to all profiles within the educational program, and profile). According to the educational standards, the student during the period of study on the educational program must acquire the entire cultural, professional and profile competences (in case of several profiles, existing in the structure of the educational program), provided in the educational plan. Respectively, the elective disciplines between which the students are allowed to choose can be characterized in the plan by one set of competences. Thus, for the construction of the students’ individual professional paths there is the need to differentiate these disciplines.To develop the tools for reaching this goal, the ontological model of the competence-oriented curriculum is constructed, and the algorithm of forming the competences, “complementary” to the competences of the curriculum is suggested. Practical application of the tools is illustrated by developing the “complementary” competences of a specific profile of education (“information management”) of the basic educational program (Bachelor in Management) of 2017 admission year in one of the leading Russian universities.Results. The main methodological result of the work is the suggested algorithm of “complementary” competences formation. The algorithm includes the following steps:1. Analysis of the existing competences of the curriculum;2. Figuring out the criteria of decomposition of the existing competences of the plan and sources of formation of the “complementary” competences;3. Formation of the “complementary” competences, allowing differentiation between the professional and profile elective disciplines;4. Mapping the formed “complementary” competences with the elective disciplines, allowing constructing the individual professional development paths.Practical approbation of the developed algorithm shows its applicability for reaching the designated objectives. Based on the formed algorithm the improved ontological model of the competence-oriented curriculum has been developed, including external sources of the “complementary” competences.Conclusion. The developed tools of differentiating between the elective disciplines of the competence-oriented curriculum have several directions of potential practical applicability. Firstly, students can use these tools for the individual professional development paths’ formation. Secondly, management of the educational programs could use these tools for upgrading the competence-based curricula. Namely, the suggested tools allow increasing logical and systemic self-consistency of the curricula without fundamentally altering their structure; in addition, the tools enable timely correction of curriculum content in accordance with changes in the needs of current and potential employers of the relevant sectors of the economy.